2013
DOI: 10.1136/postgradmedj-2012-131723
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol: ACTH ratio to test for primary hypoadrenalism: a pilot study

Abstract: Although the cortisol: ACTH ratio predicts primary hypoadrenalism, its value is limited to diagnosing primary hypoadrenalism as it does not distinguish secondary hypoadrenalism from normal adrenal function. Larger prospective studies that include patients with early primary hypoadrenalism are needed to confirm the reliability of plasma cortisol: ACTH ratio as a diagnostic test for primary hypoadrenalism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…Particularly during the chronic or prolonged phase of critical illness (rather than in the acute phase, as in the Boonen et al study [ 20 ]), low ACTH and elevated cortisol levels can be seen, suggestive of increased sensitivity to ACTH or ACTH-independent cortisol production [ 2 , 21 - 23 ]. The latter may be caused by non-ACTH pituitary stimulants or feedback suppression of ACTH after impaired cortisol metabolism and persistent hypercortisolemia [ 2 , 21 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly during the chronic or prolonged phase of critical illness (rather than in the acute phase, as in the Boonen et al study [ 20 ]), low ACTH and elevated cortisol levels can be seen, suggestive of increased sensitivity to ACTH or ACTH-independent cortisol production [ 2 , 21 - 23 ]. The latter may be caused by non-ACTH pituitary stimulants or feedback suppression of ACTH after impaired cortisol metabolism and persistent hypercortisolemia [ 2 , 21 - 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with etomidate-inhibiting adrenal cortisol synthesis, indeed, reduces the cortisol/ACTH ratio and diminishes the cortisol response to exogenous ACTH [ 16 , 19 ]. The ratio is used to diagnose primary absolute adrenal insufficiency [ 20 ]. However, Boonen et al [ 21 ] recently suggested that, during critical illness, impaired cortisol metabolism (measured in relatively few patients) contributes to elevated (free) cortisol levels and low endogenous ACTH levels via feedback inhibition, and thereby to a diminished response to exogenous ACTH in the absence of adrenal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, no patient had a ratio <3.0 suggestive of primary hypoadrenalism. 14 We found no correlation between the change in LDL-C from baseline to week 52 and the corresponding change in cortisol (Online Figure I). Cortisol, ACTH, and the cortisol:ACTH ratio also showed no significant changes in placebo-treated patients.…”
Section: Steroid Hormonesmentioning
confidence: 79%
“…We calculated cortisol:ACTH for all patients, because a ratio of <3.0 (nmol/pmol) may suggest a diagnosis of primary hypoadrenalism. 14 The primary end point of the study (percent change from baseline in ultracentrifugation LDL-C at week 52 with evolocumab when …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation